Critical Evaluation of Professional Development and Training Programs for Civil Engineers in Baghdad: Professional development - Al Mohsin, Mohammed; Al Hadithi, Bevian; Alnuaimi, Ali (Revista de la Construcción. Journal of Construction, 2018)
Construction industry comprises a high degree of competition; the performance of construction projects is highly affected by the performance of civil engineers who are the core of construction productivity. Professional development is one of the essential milestones toward improving the performance of civil engineers. This paper, critically, evaluates the professional development and training of civil engineers in Baghdad. This encompassed the study of the existing programs offered for the professional development, the expected impact, and suggestions. Data were collected from 113 professional civil engineers about the existing professional development programs and training courses and analyzed. Large variations were found in terms of the time spent for professional development, despite the fact that they are comparable to some developed countries. Pitfalls in the field of professional training and development were clear. Remedial suggestions including professional development program and appraisal system were presented. It was emphasized that collaborative efforts by all stakeholders are required to ensure sustainable professional development.